Fatal Drowning in Delta State, Nigeria: A Retrospective Study of Cases in this Region (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Drowning death is a preventable, under-reported public health problem resulting fromrespiratory insufficiency secondary to immersion or submersion in liquid.Aim: To study the sex, age, and place of death of victims of fatal drowning in Warri, Delta state, Nigeria.Material and Method: This is a descriptive, retrospective study of cases of fatal drowning reported to thecoroner and subjected to postmortem examination by the authors in Delta State from 1st January 2003 to31th December 2016. Basic information such as the age, sex and place of death were extracted and analyzedusing Microsoft Office Excel, version 2007.Results: Thirty-seven victims comprising of 34 males and 3 females were examined during this study,giving a mean incidence of about 2.5 cases per annum. Their ages ranged from 1.5 to 59 years with a meanof 28. 53 years and a dual peak in the 3rdand 4th decades. All the deaths were of accidental causes, with mostthe of them (70%) occurring within natural water bodies.Conclusion: The study showed that drowning death is relatively common and usually of accidental etiology.Young males in their thirties and forties are the most vulnerable victims, with the natural water bodies beingthe most common site of drowning. Being a preventable cause of death, adopting and enforcing preventivesafety measures by the individuals, community and government will invariably reverse this trend.